Nuclear Signaling of Plant MAPKs - Bigeard, Jean; Hirt, Heribert (Frontiers in Plant Science, 2018)
Mitogen-activated protein kinases (MAPKs) are conserved protein kinases in eukaryotes that establish signaling modules where MAPK kinase kinases (MAPKKKs) activate MAPK kinases (MAPKKs) which in turn activate MAPKs. In plants, they are involved in the signaling of multiple environmental stresses and developmental programs. MAPKs phosphorylate their substrates and this post-translational modification (PTM) contributes to the regulation of proteins. PTMs may indeed modify the activity, subcellular localization, stability or trans-interactions of modified proteins. Plant MAPKs usually localize to the cytosol and/or nucleus, and in some instances they may also translocate from the cytosol to the nucleus. Upon the detection of environmental changes at the cell surface, MAPKs participate in the signal transduction to the nucleus, allowing an adequate transcriptional reprogramming. The identification of plant MAPK substrates largely contributed to a better understanding of the underlying signaling mechanisms. In this review, we highlight the nuclear signaling of plant MAPKs. We discuss the activation, regulation and activity of plant MAPKs, as well as their nuclear re-localization. We also describe and discuss known nuclear substrates of plant MAPKs in the context of biotic stress, abiotic stress and development and consider future research directions in the field of plant MAPKs.